CLASSIFICATION CRITERIA SETS FOR RHEUMATOID ARTHRITIS: HISTORICAL PERSPECTIVE AND CLINICAL IMPLICATIONS - Gündüz, İbrahim; Karataş, Ahmet (My University, 2025)
The classification criteria for rheumatoid arthritis (RA) have undergone significant evolution since their inception, a process driven by the need to address evolving clinical requirements and shifting research priorities. To comprehensively review the historical development, comparative strengths, and limitations of major RA classification criteria sets, with emphasis on their clinical and research applications. A narrative review of the literature was conducted, examining the 1956 diagnostic criteria, 1987 American College of Rheumatology (ACR) classification criteria, 2010 ACR/European Alliance of Associations for Rheumatology (EULAR) classification criteria, and early RA classification frameworks. The 1956 criteria established the first standardized approach but presented implementation challenges. The 1987 ACR criteria demonstrated excellent specificity (87-94%) for established disease but limited sensitivity (47-58%) for early disease. The 2010 ACR/EULAR criteria resulted in a marked improvement in the early detection of disease, with higher sensitivity (62-91%) but a reduction in specificity (21-78%). Recent early RA classification frameworks have attempted to balance sensitivity (85-86%) and specificity (87-88%) specifically in early disease presentations. It is evident that each set of criteria exhibits distinct advantages, contingent on factors such as disease duration, patient population characteristics, and research objectives. Understanding the evolution and appropriate implementation of RA classification criteria is essential for both clinical research and practice. While the 2010 criteria represent significant advancement in early identification, challenges remain for seronegative patients. Incorporating imaging and novel biomarkers may further enhance classification accuracy in ambiguous presentations.
Keywords: Early diagnosis; Rheumatoid arthritis; classification criteria; American College of Rheumatology criteria; European Alliance of Associations for Rheumatology criteria; seronegative arthritis